Just Google it! Digital literacy and the epistemology of ignorance. Issue 3 (3rd April 2019) - Bhatt, Ibrar; MacKenzie, Alison
ABSTRACT: In this paper we examine digital literacy and explicate how it relates to the philosophical study of ignorance. Using data from a study which explores the knowledge producing work of undergraduate students as they wrote course assignments, we argue that a social practice approach to digital literacy can help explain how epistemologies of ignorance may be sustained. If students are restricted in what they can know because they are unaware of exogenous actors (e.g. algorithms), and how they guide choices and shape experiences online, then a key issue with which theorists of digital literacy should contend is how to educate students to be critically aware of how power operates in online spaces. The challenge for Higher Education is twofold: to understand how particular digital literacy practices pave the way for the construction of ignorance, and to develop approaches to counter it.